2013
DOI: 10.1038/bjc.2013.386
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of unknown primary: a population-based analysis of temporal change and socioeconomic disparities

Abstract: Background:Cancer of unknown primary (CUP) is the fourth most common cause of cancer death. With advanced diagnostics and treatments, we investigated the proportion of cancers diagnosed as CUP, treatment outcomes and association with socioeconomic disparities.Methods:We analysed trends in CUP diagnosis and outcome within the Surveillance, Epidemiology, and End Results registry between 1973 and 2008.Results:The percentage of all cancers diagnosed as CUP has decreased over time comprising <2% of cancers since 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 30 publications
6
75
4
1
Order By: Relevance
“…Application of a more restrictive definition of CUP results in a considerably lower estimate of incidence under 0.3 % [81][82][83][84][85]. The proportion of CUP in oral metastases varied between the studies.…”
Section: Carcinoma Of Unknown Primarymentioning
confidence: 95%
“…Application of a more restrictive definition of CUP results in a considerably lower estimate of incidence under 0.3 % [81][82][83][84][85]. The proportion of CUP in oral metastases varied between the studies.…”
Section: Carcinoma Of Unknown Primarymentioning
confidence: 95%
“…An American study found that a higher proportion of CUP was diagnosed in the elderly, females, black people and residents of less affluent or less educated counties [23]. A recent study of Scottish Cancer Registry data from 1961-2010 found that during 2001-2010, age-standardised rates of CUP were higher in the most compared with the least deprived quintile of the population [24].…”
Section: What Is Already Known On This Topic?mentioning
confidence: 99%
“…It is also possible that, for some members of this group, CUP diagnosis was used by the registry as a temporary diagnosis but was never updated, so that the final record shows unconfirmed histology. Two recent population registry studies reported CUP with no histological evidence to comprise 30.3% and 58.4% of CUP cases [15,24]. While this does not prove the accuracy of the CUP diagnosis, it does show these patients represent a significant and clinically visible subset of the CUP population.…”
Section: Discussionmentioning
confidence: 92%